Synergistic oxidation of CVD graphene on Cu by oxygen plasma etching. (December 2017) - Hui, Lok Shu; Whiteway, Eric; Hilke, Michael; Turak, Ayse
Abstract: Oxygen plasma interaction with graphene is a prime route to functionalizing for unique semiconducting and photoluminescent properties. Unlike exfoliated graphene films, chemical vapour deposited (CVD) graphene on metal show much longer and more robust response to oxygen plasma. In this study, we use Raman, ATR-FTIR and x-ray photoelectron spectroscopy to examine the behaviour of full coverage CVD graphene on Cu under various plasma and annealing treatments. Initially exposure to oxygen plasma leads to light oxygen doping, analogous to reduced graphene oxide (phase I GO). With increasing oxygen exposure, the Cu underneath the defect sites begin to oxidize, stabilizing the graphene layer. Eventually, the reduced graphene oxide undergoes a transformation into a graphene oxide-like reduced graphene oxide (phase II GO), accompanied by the complete oxidation of the Cu foil underneath. The synergistic effect of Cu and graphene oxidation by oxygen plasma means that both are stabilized, with the graphene acting as an oxygen barrier for Cu at the initial stages and the Cu preventing complete graphene destruction until significant plasma dosages are reached. The longer window of plasma induced damage due to this synergistic oxidation mechanism may be exploited to pattern nanostructures in graphene based devices. Graphical abstract: